2018
DOI: 10.1021/acs.joc.8b00517
|View full text |Cite
|
Sign up to set email alerts
|

Improved Synthesis of 4-Cyanotryptophan and Other Tryptophan Analogues in Aqueous Solvent Using Variants of TrpB from Thermotoga maritima

Abstract: The use of enzymes has become increasingly widespread in synthesis as chemists strive to reduce their reliance on organic solvents in favor of more environmentally benign aqueous media. With this in mind, we previously endeavored to engineer the tryptophan synthase β-subunit (TrpB) for production of noncanonical amino acids that had previously been synthesized through multistep routes involving water-sensitive reagents. This enzymatic platform proved effective for the synthesis of analogues of the amino acid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 24 publications
0
70
0
Order By: Relevance
“…Many substituted indoles and even other amino acids can participate in this versatile reaction, which affords access to complex starting materials for downstream modification . Recently, these efforts have been made even easier by evolving the β‐subunit of tryptophan synthase (TrpB; EC 4.2.1.20) for efficient stand‐alone function . These engineered TrpBs can operate at high temperatures, which is helpful in solubilizing hydrophobic indoles, and provide access to highly complex Trp analogues in good yield.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many substituted indoles and even other amino acids can participate in this versatile reaction, which affords access to complex starting materials for downstream modification . Recently, these efforts have been made even easier by evolving the β‐subunit of tryptophan synthase (TrpB; EC 4.2.1.20) for efficient stand‐alone function . These engineered TrpBs can operate at high temperatures, which is helpful in solubilizing hydrophobic indoles, and provide access to highly complex Trp analogues in good yield.…”
Section: Methodsmentioning
confidence: 99%
“…To test the promiscuity of Rgn TDC, we sought to measure its kinetic parameters with a complete set of 4‐, 5‐, 6‐, and 7‐chlorotryptophans; however, the requisite enantiopure chlorotryptophans were not readily available. We therefore prepared each Trp analogue from its indole precursor through a simple biocatalytic reaction by using engineered TrpBs from Pyrococcus furiosus with high stand‐alone activity . Surprisingly, the kinetic parameters of Rgn TDC with each chlorotryptophan showed only modest decreases in catalytic efficiency when compared to the native Trp substrate (Table , Figure S3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant effect of the E104(105)G mutation suggested that this conserved catalytic residue might be playing an important role in the non‐native azulene reaction. We explored this possibility by examining two engineered variants with and without the E104(105)G mutation: Pf 5G8, which exhibits optimal activity at 75 °C, and Tm 9D8*, which exhibits optimal activity at lower temperatures such as 37 °C . Challenging the enzymes with indole demonstrated that this mutation only modestly decreases the rate of Trp formation (Figure ), with an additional slight decrease in the chemoselectivity of the reaction that leads to the formation of trace amounts of isoTrp (a product of the N‐alkylation of indole, shown in Figure S2 and described previously).…”
Section: Methodsmentioning
confidence: 99%
“…2 We evolved this enzyme to accept a variety of indole analogues and nitroalkanes with activated sp³-carbon atoms as nucleophiles ( Figure 1b). [3][4][5][6][7][8] However, these studies revealed limitations including chemo-and stereoselective control we would need to address in order to realize TrpB's broad potential as a biocatalyst for C-C bond formation. Previous biocatalytic reactions catalyzed by variants of TrpB [5][6]8 and proposed stereo-and chemo-selective reaction using engineered TrpB.…”
Section: Introductionmentioning
confidence: 99%